MOSSES DIVERSITY IN GROJOGAN SEWU, JUMOG, AND PARANG IJO WATERFALL, KARANGANYAR DISTRICT - Mustaqim, Salwa Nazhifah; Sugiharto, Bowo (Universitas Medan Area, 2025)
Moss is a plant that can be found in low and highlands and lives attached to the substrate. The purpose of this study was to determine the diversity of lichens that grow in waterfalls located in Karanganyar district. The method used in this research was purposive sampling method. Based on the observations of the species found came from 5 classes namely Bryopsida, Marchantiopsida, Anthecerotopsida, Hepaticopsida and Jungermanniopsida. The level of diversity in each waterfall is influenced by environmental factors such as temperature, humidity and sunlight. Jumog and Parang ijo waterfalls have a high diversity index, while the evenness value of the three waters is high, and has the same dominance value which is classified as low.